Pengaruh Beban Kerja dan Employee Engagement terhadap Kinerja Karyawan PT Taspen (Persero) - Ika Marliana Putri (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
Employee performance is an important aspect in maintaining service quality, especially in a service unit that directly interacts with participants. This study aims to examine the effect of workload and employee engagement on employee performance at PT Taspen (Persero). The research used a quantitative associative approach. The population consisted of 40 employees in the service division of PT Taspen (Persero) in the Jabodetabek area. A saturated sampling technique was applied, so all members of the population were used as respondents. Data were collected through questionnaires, observation, interviews, and literature study. The data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, t-test, F-test, and the coefficient of determination using IBM SPSS Statistics version 25. The results show that workload has a positive and significant effect on employee performance, with a significance value of 0.000. Employee engagement also has a positive and significant effect on employee performance, with a significance value of 0.038. Simultaneously, workload and employee engagement have a significant effect on employee performance, with a significance value of 0.000. The R Square value of 0.494 indicates that workload and employee engagement explain 49.4% of employee performance variation.